THE ROLE OF JOB SATISFACTION IN MEDIATING THE INFLUENCE OF MOTIVATION AND ORGANIZATIONAL CULTURE TOWARD TEACHER PERFORMANCE IN INSTITUT INDONESIA 48 SEMARANG FOUNDATION - Adi, Susilo; Basiya, R (Jurnal Ilmiah Telaah Manajemen, 2017)
The purpose of this study is to: Examine and analyze the influence of motivation on job satisfaction ofteachers; Examine and analyze the influence of organizational culture on job satisfaction of teachers;Examine and analyze the influence of motivation on teacher performance; Examine and analyze theinfluence of organizational culture on teacher performance; Examine and analyze the effects of jobsatisfaction on teacher performance; Examine and analyze whether job satisfaction mediates theeffect of motivation on teacher performance; Examine and analyze the job satisfaction mediates theinfluence of organizational culture on teacher performance.The type of this research is explanatory research, using a quantitative approach. The populations inthis research are 80 teachers in Yayasan Institut Indonesia 48 Semarang. Samples were taken usingcensus method, so use the whole amount of the population as the object of research. The techniquesof data analysis use multiple linear regression, fit model test, determination coefficient (R2) test,classic assumption test, hypothesis test (t test), and test for the mediating effect.The results showed that; Work motivation does not influent job satisfaction; Organizational culturepositively and significantly influents job satisfaction; Work motivation positively and significantlyinfluents teacher performance; Organizational culture does not influence the teacher performance;Job satisfaction positively and significantly influents teacher performance; Job satisfaction mediatesthe influence of organizational culture on teacher performance but does not mediate the influence ofwork motivation toward teacher performance.Keywords: Work Motivation, Organizational Culture, Job Satisfaction and Teacher Performance